2023
DOI: 10.1002/jad.12139
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional microaggressions, depressive symptoms, and the role of LGBTQ‐specific parental support in a sample of Latinx sexual and gender minority youth

Abstract: Introduction: Latinx and sexual and gender minority (SGM) youth experience higher incidents of racism, cissexism, and heterosexism in the forms of overt discrimination and microaggressions. These experiences could in part explain increased negative mental health outcomes, such as depressive symptoms. Evidence points to the possibility that LGBTQ-specific parental support buffers the effects of intersectional microaggressions on depressive symptoms among Latinx SGM youth. Methods: In a sample of 1292 Latinx SGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…Researchers examining the effects of racial microaggressions have found strong evidence that these exchanges have a detrimental impact on psychological and physiological well-being (Abreu et al, 2023 ; Barrita et al, 2023a ; Barrita et al, 2023b ; Wong-Padoongpatt & Barrita, 2022a ). For instance, Wong-Padoongpatt et al ( 2017 ) experimentally tested the causal effects of microaggressions and found that Asian people who experienced a racial microaggression about English abilities showed increased physiological stress.…”
Section: “Alien In One’s Own Land”: Racial Microaggressions For Latin...mentioning
confidence: 99%
“…Researchers examining the effects of racial microaggressions have found strong evidence that these exchanges have a detrimental impact on psychological and physiological well-being (Abreu et al, 2023 ; Barrita et al, 2023a ; Barrita et al, 2023b ; Wong-Padoongpatt & Barrita, 2022a ). For instance, Wong-Padoongpatt et al ( 2017 ) experimentally tested the causal effects of microaggressions and found that Asian people who experienced a racial microaggression about English abilities showed increased physiological stress.…”
Section: “Alien In One’s Own Land”: Racial Microaggressions For Latin...mentioning
confidence: 99%
“…with only one structurally marginalized trait (e.g., Latine cisgender youth; Abreu et al, 2023), and they are more negatively impacted by these experiences (Barrita et al, 2023). The concept of microaggressions has been scrutinized as simply being a less severe form of prejudice and discrimination (Barber et al, 2020); however, these experiences present unique tribulations for the recipient, including feelings of frustration, loss of selfesteem, self-stigmatization, and alienation (Gonzales, Davidoff, Nadal, et al, 2015;Peters et al, 2017).…”
Section: Microaggressionsmentioning
confidence: 99%
“…Department of Justice, 2022). However, it is important to acknowledge the large body of work that has examined the experiences of microaggressions and their detrimental effects on health among other ethnic/racial minorities (e.g., Hispanic/Latinx Americans; Abreu et al, 2023; Chakraverty, 2022; Sanchez et al, 2018) and other minoritized identities (e.g., lesbian, gay, bisexual, transgender, queer; Vaccaro & Koob, 2019). Prior research has found that microaggressions experienced by Asian and Black Americans were consistent with racial and ethnic stereotypes that occur in the United States (Forrest-Bank & Jenson, 2015).…”
Section: Cognitive Reappraisal As a Moderator Of The Link Between Mic...mentioning
confidence: 99%
“…The present study focuses on the microaggressions experienced by Asian and Black Americans given the increase of hate crimes and discrimination attributed to the COVID-19 pandemic among Asian Americans (Gover et al, 2020), the murder of George Floyd on May 25, 2020, and an increase in anti-Asian and anti-Black incidents from 2019 to 2020 (Federal Bureau of Investigation, n.d.; U.S. Department of Justice, 2022). However, it is important to acknowledge the large body of work that has examined the experiences of microaggressions and their detrimental effects on health among other ethnic/racial minorities (e.g., Hispanic/Latinx Americans; Abreu et al, 2023;Chakraverty, 2022;Sanchez et al, 2018) and other minoritized identities (e.g., lesbian, gay, bisexual, transgender, queer;Vaccaro & Koob, 2019). Prior research has found that microaggressions experienced by Asian and Black Americans were consistent with racial and ethnic stereotypes that occur in the United States (Forrest-Bank & Jenson, 2015).…”
mentioning
confidence: 99%